Essential hypertension in the pathogenesis of age-related macular degeneration: a review of the current evidence. Issue 12 (December 2015) - Katsi, Vasiliki K.; Marketou, Maria E.; Vrachatis, Dimitrios A.; Manolis, Athanasios J.; Nihoyannopoulos, Petros; Tousoulis, Dimitrios; Vardas, Panos E.; Kallikazaros, Ioannis
Abstract : Age-related macular degeneration (AMD) is one of the main causes of vision loss, especially in the elderly. The involvement of essential hypertension in its pathogenesis has been well covered in the literature since it was first recognized. Hemodynamic abnormalities appear to contribute to AMD, with the renin–angiotensin system playing a significant role. Many studies have demonstrated that high blood pressure is associated with lower choroidal blood flow and disturbed vascular homeostasis in these patients. In addition, AMD is characterized by abnormal neovascularization, to which angiotensin II and growth factors make a large contribution. Most epidemiological studies have found essential hypertension to be a risk factor for AMD. However, although all agree that the strongest predisposing factors are age and smoking, overall there is some inconsistency regarding the exact role of hypertension in its pathogenesis. In particular, there are no data in the literature to support the view that antihypertensive medication and the successful management of hypertension have a positive effect on the clinical outcome of AMD. This reinforces the data indicating that the cause of AMD is multifactorial and suggests that, although essential hypertension probably plays a role, in itself it is unlikely to be a major contributor to the future occurrence of AMD.